Aplikasi Pengolahan Citra Digital Menentukan Bobot Sapi Dengan Metode Titik Berat Berbasis Android - Mahendra, Vicki Yuda; Riadi, Aditya Akbar; Evanita, E (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2022)
Cattle is a consumption animal that is in great demand by Indonesians, its soft meat and delicious taste make beef one of the most expensive meats at the moment, cattle breeders are now starting to modernize and continue to develop their farms to make it easier to maintain and sell cattle, in this modern era there are many things that are facilitated by technology that makes it easier for people to do things, one of which is calculating the weight of a cow with an android application by entering an image of a cow that will be processed and will produce a value for the size and weight of the cow. The weight of the cow can be calculated using the Schoorl formula and the Modified/ Lambourne formula which requires variables of body length and chest circumference for calculation. To get bodyweight, it is necessary to measure chest circumference and body length which are measured manually. However, the reality in the field shows that to get the values for chest circumference and body length, manual measurements need to be carried out, and this is not easy to do because cows are difficult to condition. In the field itself, there is no practical and accurate tool to calculate chest circumference, body length, and weight of cows. Starting from this problem, gave rise to the idea of making a tool that can measure accurately and easily.